Les métamorphoses du monde : sociologie de la mondialisation - Martin, Dominique; Metzger, Jean-Luc; Pierre, Philippe (Paris : Seuil, 2003)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: globalisering